Pengaruh Kesalahan Berbahasa Indonesia Terhadap Kualitas Penulisan Akademik Pada Mahasiswa Pendidikan Administrasi Perkantoran Di Universitas Negeri Medan - Dina Girsang; Fanny Pakpahan; Martha Sianturi; Oshinta Simanullang; Yulia Siburian; Yusi Putri; Muhammad Anggie Januarsyah Daulay (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to investigate the influence of Indonesian language errors on the quality of academic writing among students of the Office Administration Education Study Program at Universitas Negeri Medan. As future professionals, students are required not only to master administrative competencies but also to develop the ability to express ideas in clear and correct academic writing. Academic writing plays a vital role in higher education, as it reflects students’ logical thinking, systematic reasoning, and professional skills. However, preliminary observations indicate that many students still commit frequent errors in the use of Indonesian, including spelling, diction, sentence structure, and cohesion–coherence, all of which contribute to a decline in the overall quality of their academic texts. The study employed a descriptive quantitative approach with a correlational method. Data were collected from 30 students selected through purposive sampling. Two research instruments were used: a questionnaire consisting of 15 items designed to measure students’ frequency of language errors, and a rubric-based assessment of their academic writing, which evaluated five aspects: spelling, diction, sentence structure, cohesion-coherence, and academic style. The findings revealed that most students (60%) fell into the moderate error category, while 13.3% belonged to the low-error category and 26.7% to the high-error category. The average score of academic writing quality was 51.4, showing considerable variation among individuals. Pearson’s correlation analysis indicated a very strong and significant negative relationship between language errors and academic writing quality (r = -0.88, p < 0.01). The results suggest that the higher the frequency of language errors, the lower the quality of students’ academic writing. Therefore, strengthening students’ mastery of Indonesian linguistic rules is essential in improving their academic performance. Structured training in academic writing and systematic feedback from lecturers are strongly recommended to enhance students’ competence.